Effectiveness of a nursing intervention during transfusion of packed red cells on the patient´s anxiety state receiver - Jesús Fernando Martín Díaz; Mª Jesús Hidalgo Gutiérrez; Mª Fátima Cerezo Solana; Mª José Casas Carriazo; Jaime Martín Morcillo (Fundación para el Desarrollo de la Enfermería, 2012)
The transfusion provokes anxiety and this one compromises the improvement of the patient. Objetive: The study aims to evaluate whether a nursing intervention protocol-through oral and written submissions previous to the transfusion of packed red blood cells decreases anxiety levels in pretransfusion and postransfusion recipient patients through a randomized clinical trial. Methodology: Be conducted in patients over 18 years admitted in the Hospitable complex of Toledo, prescription transfusion of packed red blood cells. For an alpha error 0.05, beta error of 0.90, with an expected effect of 10%, need 70 subjects in each group. The allocation to the intervention group and the control group was randomly made simple. The performance in the normal control group will be done in the hospital, patients receiving transfusion. As dependent variables evaluated:- The anxiety level pretransfusion and postransfusion. Using the questionnaire was validated by Spielberger (STAI). - The level of satisfaction perceived by the user on the information received prior to transfusion. By design developed for this study. Also recorded other control variables: sex, age, socio-cultural level, marital status, reason for transfusion, or no knowledge of the prescription of transfusion, incidents during transfusion.Scientific and sociosanitary relevancy of the study: The results will allow to know if the transfusion increases the anxiety and if an educational intervention nurse can diminish it; and to do the intervention before every transfusion.